Large herbivore responses to water and settlements in savannas - Ogutu, Joseph O.; Piepho, Hans-Peter; Reid, Robin S.; Rainy, M.E.; Kruska, Russell L.; Worden, J.S.; Nyabenge, M.; Hobbs, N.T. (Wiley, 2010)
Sustaining wildlife and pastoral communities in savannas worldwide depends on understanding how landscapes provide for their needs. The composite effects of multiple forces shape herbivore distribution in savannas. We propose a model describing the distribution of animal density along two resource utilization gradients. The model estimates where animals are most abundant in relation to water and pastoral settlements and how strongly they respond to these gradients, as indicated by the location of peak densities in landscape space and degree of attraction of animals to these locations. We use the model to show that distances to water and settlements interactively influence the distribution of wild herbivore and livestock densities in a semiarid protected and pastoral African savanna. The herbivores were distributed along distance from water and settlement gradients according to four distinct patterns, suggesting the preponderance of constrained foraging. The impact of distance to water and settlement on herbivore distribution was modified by land use type and temporal variation in rainfall, and also varied among different species of wildlife and between wildlife and livestock. Wild herbivores peaked in density farther from settlements than from water and were much more strongly attracted to their points of maximum density in the pastoral than in the protected land. The point of maximum density was farther removed from settlements in the protected than in the pastoral landscape where the wild herbivores were compressed into smaller suitable habitats. The interaction between distances from settlement and water produced discernible spatial segregation among species in terms of the locations of their points of maximum density, presumably to minimize interspecific competition for forage and water. Settlements exerted relatively stronger influence on livestock distribution than water, resulting in densities that declined exponentially away from settlements at all distances from water.